Islamic marketing and consumer behaviour: a systematic literature review. Issue 6 (14th October 2019) - Floren, Jessen; Rasul, Tareq; Gani, Azmat
Abstract : Purpose: The purpose of this study is to systematically review the existing literature on Islamic marketing and its major impacts on consumer behaviours. In addition, this study seeks to shed light on global trends and dynamics beyond Islamic marketing and how Islam, as one of the most prominent religions worldwide, affects the consumption and purchasing choices of Muslim consumers. Design/methodology/approach: A systematic literature review of published peer-reviewed articles on Islamic marketing was conducted. A comprehensive search strategy was applied on different databases, including Google Scholar, JSTOR, ScienceDirect, MUSE and Directory of Open Access Journals, and the retrieved articles were then selected from 14 leading journals published between 2010 and 2018. Findings: Islam as a religion has been found to impact the ethical beliefs and behaviours of Muslim consumers from different countries, as well as consumers' choice of services and some taboo products on the basis of Islamic Shariah law. The results show that Islamic marketing has a significant impact on the characteristics of Muslim consumers and therefore affects their key choices about certain products and services. Research limitations/implications: The studies included in this review are extensively based on peer-reviewed articles published in high-ranked marketing journals (A* and A in the Australian Business Deans Council list), which may be perceived as a limitation in the present study. Another limitation is that this study only took into account peer-reviewed articles written in English. Practical implications: The important relationship between Islam and the heterogeneous Muslim consumer will have a considerable practical implication for companies that explore the marketing supply capacity in the Islamic world. The authors hereby expect the current review to significantly impact the identification of methodologies for the main trends in the academic analysis of Islamic marketing and Islamic consumer behaviour. Originality/value: This review provides a strong contribution to Islamic marketing literature by recommending the need to integrate the Islamic practices related to consumer consumption of goods and services in studies focused on consumer behaviour analysis.